Coral reef productivity and diversity—Contributions from enhanced photosynthesis via demand for carbohydrate from the host. (25th October 2020) - Adams, Melanie S.; Demmig‐Adams, Barbara; Li, Ruiqi; Zarate, Daniel; Li, Jingchun
Abstract: Coral reefs' high productivity has been attributed mainly to photosymbioses between the coral animal and algae of the family Symbiodiniaceae, with recognition that the host can increase algal photosynthesis by concentrating nutrients and enhancing the efficiency of light absorption. Here, we propose that an additional effect, consumption of carbohydrate by the host, may also enhance algal photosynthesis. We examine evidence from symbiosis between terrestrial plants and root fungi that indicates a link between carbohydrate consumption by the symbiotic partner and photosynthetic upregulation in the plant system. In addition, we review evidence from free‐living algae manipulated to exude carbohydrate into the external medium, which was associated with strong upregulation of photosynthetic capacity. We offer suggestions on how host‐induced carbohydrate release may increase photosynthesis rates in the symbionts in the intact photosymbiosis and how this relationship evolved.